Collaborative information monitoring: Preliminary results of a systematic mixed studies review and a framework synthesis. Issue 1 (22nd October 2020) - Granikov, Vera; El Sherif, Reem; Bouthillier, France; Pluye, Pierre
Abstract: Keeping up to date is essential across professional fields, yet it remains a challenge. Collaboration may act as a facilitator, yet more knowledge is needed to see if, how, and why it could overcome the challenges of keeping up to date. This systematic mixed studies review, a work in progress, bridges the conceptual fields of information monitoring/environmental scanning with collaborative information seeking. Specifically, a "best fit" framework synthesis approach is used to identify potential factors and outcomes, and to adapt a model of environmental scanning to collaborative information monitoring.